2021
DOI: 10.1186/s13073-021-00861-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of double-positive thymocytes at single-cell resolution

Abstract: Background T cells generated from thymopoiesis are essential for the immune system, and recent single-cell studies have contributed to our understanding of the development of thymocytes at the genetic and epigenetic levels. However, the development of double-positive (DP) T cells, which comprise the majority of thymocytes, has not been well investigated. Methods We applied single-cell sequencing to mouse thymocytes and analyzed the transcriptome da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 53 publications
1
24
1
Order By: Relevance
“…A similar but delayed pattern is seen in expression of cleaved-PARP1 (cPARP), which is produced during both apoptosis and necrosis(Elmore, 2007) (Figure 6C). Proliferation, identified by IDU incorporation, also exhibits a bi-wave profile, where cells divide more extensively around day 5 during the third phase of the DN state (DN3)(Laurent et al, 2004; Paiva et al, 2021), and then again at the DP state(Ciofani and Zúñiga-Pflücker, 2007; Li et al, 2021) between days 15 and 20 (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar but delayed pattern is seen in expression of cleaved-PARP1 (cPARP), which is produced during both apoptosis and necrosis(Elmore, 2007) (Figure 6C). Proliferation, identified by IDU incorporation, also exhibits a bi-wave profile, where cells divide more extensively around day 5 during the third phase of the DN state (DN3)(Laurent et al, 2004; Paiva et al, 2021), and then again at the DP state(Ciofani and Zúñiga-Pflücker, 2007; Li et al, 2021) between days 15 and 20 (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Proliferation, identified by IDU incorporation, also exhibits a bi-wave profile, where cells divide more extensively around day 5 during the third phase of the DN state (DN3) (Laurent et al, 2004;Paiva et al, 2021), and then again at the DP state (Ciofani and Zúñiga-Pflücker, 2007;Li et al, 2021) between days 15 and 20 (Figure 6B).…”
Section: A Real-time Trajectory Recognizes Dynamics Overseen Using Ps...mentioning
confidence: 99%
“…However, it should be noted that while DN thymocytes undergo a rapid and extensive proliferative phase (6-8 cell cycle division) to ensure the generation of a large pool of progenitors, DP cells enter a resting phase to allow rearrangement of the TCR alpha chain (Taghon et al , 2006; Ciofani & Zúñiga-Pflücker, 2007). Indeed, by performing single cell RNA-seq analyses Li et al found that up to 40% of intermediate SP were in the M/G1 phase, while this was not the case for DP blasts (Li et al , 2021). Thus, it could be speculated that deletion of Sin3A at the DN stage (Cowley et al , 2005) results in the selection of a cell subset capable to survive positive thymic selection, and yet lacking proper responsiveness at the mature stage.…”
Section: Discussionmentioning
confidence: 99%
“…The final cell clusters were identified using Seurat 'FindNeighbors' and 'FindClusters' (with Louvain Algorithm option) functions with the first 20 PCs and coarse grain resolution of 0.7. Each computed cell clusters were assigned to thymopoiesis stages by manual curation, using thymopoiesis stage markers previously identified (19)(20)(21)(22) and Immgen Database (23). To infer pathway activity, genes sets of pathways of interest (Supplementary Table 2) were retrieved from Molecular Signature Database (MSigDB) (24) and were used to score pathway activity for each cell with AUCell version 1.12.0 (25).…”
Section: Single-cell Rna Sequencing Data Analysismentioning
confidence: 99%
“…After sequencing data preprocessing, which includes the removal of poor quality cells, of celldoublets and non-T cells (see Materials and Methods, Single-Cell RNA Sequencing Data Analysis), we projected the data using the UMAP non-linear dimensionality reduction method that enabled us to visualize cell transcriptome heterogeneity (17) (Figure 1B). We identified 8 clusters and assigned them to cell type according to established markers of thymopoiesis (19)(20)(21)(22)(23) (Figures 1C, D; see also Supplementary Figure 2 for unsupervised cluster gene markers). Cluster 1 encompasses DN, ISP and DP blast cells, cluster 2 corresponds to DP small , cluster 4 to DP CD69+ cells, and cluster 5 to naive CD4 + cells.…”
Section: Scrna-seq Analysis Identifies Lower Calcium Pathway Activity...mentioning
confidence: 99%